Implementasi Penanganan Terhadap Peredaran Narkotika Jenis Shabu Di Wilayah Hukum Kepolisian Resor Indragiri Hilir (Studi Kasus Perkara Nomor: LP/A/50/VIII/2025/SPKT. Satres.Narkoba/Polres.Inhil) - Ryan H; Vivi Arfiani Siregar; Kms Novyar Satriawan F (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2025)
This study aims to analyze the implementation of handling methamphetamine trafficking within the jurisdiction of the Indragiri Hilir Resort Police based on Case Number LP/A/50/VIII/2025/SPKT.Satres.Narkoba/Polres.Inhil and to identify the obstacles encountered during its implementation. This research employed an empirical legal research method using both normative juridical and empirical juridical approaches with a descriptive-analytical design. Data were collected through interviews, observations, and document studies, then analyzed qualitatively using a deductive approach. The findings indicate that the handling of the case was carried out in accordance with Law Number 35 of 2009 on Narcotics through the stages of investigation, inquiry, arrest, search, seizure, examination of witnesses and suspects, and submission of the case file to the public prosecutor. The main obstacles include limited personnel and facilities, difficulties in proving offenses, low public participation, increasingly sophisticated criminal methods, and geographical conditions. These challenges are addressed through inter-agency coordination, investigator capacity building, technological support, and public legal awareness programs to enhance the effectiveness of narcotics law enforcement.